Synthesis, Antiviral and Cytostatic Activity of New Series of Naphthalimide Derivatives - Katarzyna Gawron; Dorota G. Piotrowska; Graciela Andrei; Dominique Schols; Robert Snoeck; Iwona E. Głowacka (Polskie Towarzystwo Farmaceutyczne, 2023)
A new series of N-(diethylphosphonoalkyl)-1,8-naphthalimides were synthesized via direct reaction of 1,8-naphthalic anhydride or its 3-nitro- and 4-bromo- derivatives with selected ɷ-aminoalkylphosphonates and evaluated against a broad-spectrum of viruses as well as for their cytostatic properties toward selected cell lines. N-(diethylphosphonomethyl)-3-nitro-1,8-naphthalimide 15a exhibited inhibitory activity toward coxsackie virus B4 in Vero cells (EC50 = 9.45 μM), whereas 3-nitro-1,8-naphthalimides 15b and 15d containing short 2-carbon linker showed moderate activity against herpes simplex virus-2 (G) and herpes simplex virus-1 TK- KOS ACVr. Furthermore, compounds 15a, 15b and 15d showed antiviral potency against human coronavirus. Several naphthalimides exhibited cytostatic activity toward tested cancerous cell lines as well as normal retina cells. Transformation of selected diethyl phosphonates 13, 14 and 15 into ammonium phosphonates 21, 22 and 23 improved the solubility, however, did not result in the enhancement of antiviral and cytostatic potency of the compounds.